Low-Volume Brachial Plexus Block Providing Surgical Anesthesia for Distal Arm Surgery Comparing Supraclavicular, Infraclavicular, and Axillary Approach: A Randomized Observer Blind Trial. (21st November 2016) - Vazin, Mojgan; Jensen, Kenneth; Kristensen, Danja L.; Hjort, Mathias; Tanggaard, Katrine; Karmakar, Manoj K.; Bendtsen, Thomas F.; Børglum, Jens
Abstract : Background . Distal arm surgery is widely performed under regional anesthesia with brachial plexus block. The preponderance of evidence for the efficacy relies upon injection of local anesthetic in excess of 30 mL. We aimed to compare three different ultrasound-guided brachial plexus block techniques restricting the total volume to 20 mL. Methods . 120 patients were prospectively randomized to ultrasound-guided brachial plexus block with 20 mL ropivacaine 0.75% at either the supraclavicular, infraclavicular, or axillary level. Multiinjection technique was performed with all three approaches. Primary outcome measure was performance time. Results . Performance time and procedural pain were similar between groups. Needle passes and injection numbers were significantly reduced in the infraclavicular group (P < 0.01 ). Nerve visibility was significantly reduced in the axillary group (P = 0.01 ). Success-rate was significantly increased in the supraclavicular versus the axillary group (P < 0.025 ). Total anesthesia-related time was significantly reduced in the supraclavicular compared to the infraclavicular group (P < 0.01 ). Block duration was significantly increased in the infraclavicular group (P < 0.05 ). No early adverse effects occurred. Conclusion . Supraclavicular and infraclavicular blocks exhibited favorable characteristics compared to the axillary block. Supraclavicular brachial plexus block with the multiinjection intracluster technique exhibited significantly reduced total anesthesia-related time and higher success rate without any early adverse events.